Integrated transcriptome and metabolome analysis reveals molecular responses of the clams to acute hypoxia. (June 2021) - Sun, Xiujun; Tu, Kang; Li, Li; Wu, Biao; Wu, Lei; Liu, Zhihong; Zhou, Liqing; Tian, Jiteng; Yang, Aiguo
Abstract: Mudflat shellfish have evolved well-adapted strategies for coping with dynamic environmental fluxes and stressful conditions, including oxygen availability. The Manila clams Ruditapes philippinarum are worldwide cultured shellfish in marine intertidal zone, which usually encounter great risk of acute hypoxia exposure in coastal habitats. To reveal the effects of acute hypoxia on metabolic changes of the clams, we performed the integrated analysis of transcriptomics and metabolomics to investigate the global changes of genes and metabolites during acute hypoxia stress at the whole-organism level. The comparative transcriptome analysis reveals that the clams show the remarkable depression in a variety of biological performance, such as metabolic rates, neuronal activity, biomineralization activity, and cell proliferation and differentiation at the hypoxic condition. The metabolomic analysis reveals that amino acid metabolism plays a critical role in the metabolic changes of the clams in response to acute hypoxia. A variety of free amino acids may not only be served as the potential osmolytes for osmotic regulation, but also may contribute to energy production during the acute hypoxia exposure. The metabolite analysis also reveals several important biomarkers for metabolic changes, and provides new insights into how clams deal with acute hypoxia. These findings suggest that clams may get through acute hypoxia stress by the adaptive metabolic strategy to survive short-period of acute hypoxia which is likely to occur in their typical habitat. The present findings will not only shed lights on the molecular and metabolic mechanisms of adaptive strategies under stressful conditions, but also provide the signaling metabolites to assess the physiological states of clams in aquaculture. Graphical abstract: Image 1 Highlights: Metabolomics and transcriptomics were applied to reveal molecular responses of the clams to acute hypoxia. The clams survive short-period of acute hypoxic stress by the remarkable depression in biological process. Amino acids may not only be served as potential osmolytes, but also contribute to energy production in response to hypoxia. The metabolic adaptation to hypoxia is regulated by starch and sucrose metabolism, carnitine metabolism, and sphingolipid.